THE STRATEGY OF CONFLICT RESOLUTION INTEGRATION IN LEARNING PRACTICE IN ELEMENTARY SCHOOL (International Conference on Elementary Education, 2018)
The social phenomena which arises in the life of Indonesian society in last three decades is experiencing the process of character loss and Indonesian identity demoralization, starting from behavioral morality and socio cultural of a nation. The sense of solidarity and social empathy has began to fade, the behavior which usually friendly and helpful change into selfish and temperamental behavior. The idea of conflict resolution becomes literature to place multiculturalism which is identified by the tolerance life order toward people who are different from themselves. The Conflict resolution integration is a strategy of conflict resolution and seeks to find together the solution of conflict resolution. The strategy of conflict resolution which aims to educate students capable to overcome or resolve conflict constructively.